Analisis Wacana Kritis terhadap Pemberitaan Akun Fufufafa di Media Tempo.co - Rahadi, Arya Eka; Permadi, Didi; Edy, Sarwo (Universitas Tribhuwana Tungga Dewi, 2025)
The reporting of the â€œFufufafaâ€ account, which allegedly belongs to Gibran Rakabuming Raka, has become a viral issue on social media X and has received national attention. The news can shape public opinion among the community. This study aims to analyze the news of the â€œFufufafaâ€ account on the online media Tempo.co. This study uses the Qualitative Descriptive method with a critical discourse analysis approach outlined by Norman Fairclough. Data was collected using the literature review technique to select the micro element of â€œtext analysisâ€, mezzo â€œnews production and distribution processâ€, and macro â€œsocio-political contextâ€, then conducting critical discourse analysis. At the micro level, the use of grammar, cohesion, and coherence was found to reinforce a particular narrative about Vice President Gibran Rakabuming Raka. The mezzo element shows the wide distribution of news through digital platforms, significantly influencing public opinion. At the macro level, this news reflects the complex relationship between the media, politics, and the digital space, which influences social perceptions of certain political issues such as the many accusations against Gibran for owning a fufufafa account. This study concludes that the tempo.co media tends to present news that tarnishes Gibran's positive image, as reflected in the use of more complex syntactic words, because cohesion and coherence focus more on in-depth main issues.Pemberitaan akun